English Teachers' Online Teaching Difficulties at Senior High School 1 Payakumbuh Districts - Ifna Nifriza (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2022)
Abstract: This research was conducted to find out the difficulties faced by English teachers in teaching English through online class at SMA Negeri 1 Kec. Payakumbuh. The participants of this research are four English teachers. Qualitative descriptive design is used in this research. The purpose of this research was to describe difficulties faced by English teachers in teaching English through online class. Instrument data of this research was interviewed. The results of this research showed that the difficulties faced by English teachers in teaching English through online class as follows; lack of students’ motivation and engagement, unstable internet connection and limited quota, time consuming to prepare materials of online class, the absence of a representative online class platform, and needs for professional development and trainings. New difficulties were found in this research, decreased interaction among teachers, shortage of time, lack of recognition students’ characters and lack of a fair assessment. Keywords: online class, teaching english, difficulties.